PERBEDAAN DAYA HIDUP NYAMUK Aedes aegypti SETELAH DIPAPAR LC50 EKSTRAK BANGLE (Zingiber purpureum) DAN ANTI NYAMUK CAIR BERBAHAN AKTIF D-ALLETHRIN DAN TRANSFLUTRIN - Yulia Nur Hasanah; Nur Endah Wahyuningsih; Yusniar Hanani D. (Jurnal Kesehatan Masyarakat (Undip), 2015)
Dengue hemorrhagic fever is a disease caused by the dengue virus and transmitted by Aedes aegypti. Mostly, mosquito control uses synthetic insecticides that can cause resistance in mosquitoes and pollution in the environment so we can choose alternative natural insecticides from plants such as bangle (Zingiber purpureum) which contain essential oils, saponins, flavonoids, tannins and resins. This study aimed to analyze the difference vitality of Aedes aegypti L. after exposed LC50 bangle extract (zingiber purpureum Roxb.) and liquid mosquito insecticides d-allethrin and transflutrin. This study was a true experiment with post test only group design used Aedes aegypti population with aged 2-5 days are reared in B2P2VRP Laboratory in Salatiga, Central Java and use 900 mosquitoes for samples. Results of probit analysis LC50 of bangle extract was 660.000 ppm, d-allethrin was 36 ppm and transfluthrin was 27 ppm. The study showed difference of longevity Aedes aegypti among control and exposed group bangle, bangle and d-allethrin, bangle and transfluthrin (p = 0.0001)(Post Hoc, Tukey). There was no difference of  Aedes aegypti longevity among the control, d-allethrin (p = 0.074) and transfluthrin (p = 0.999), moreover there was also no difference of Aedes aegypti longevity between  exposed group d-allethrin and transfluthrin (p = 0.094). The result showed no difference the number of surviving Aedes aegypti among control, exposed group of bangle, d-allethrin and transfluthrin (p = 0,607) (Kruskal Wallis).